Detecting early signs in Duchenne muscular dystrophy: comprehensive review and diagnostic implications - Mercuri, Eugenio; Pane, Marika; Cicala, Gianpaolo; Brogna, Claudia; Ciafaloni, Emma (Frontiers in Pediatrics, 2023)
Despite the early onset of clinical signs suggestive of Duchenne muscular dystrophy (DMD), a diagnosis is often not made until four years of age or older, with a diagnostic delay of up to two years from the appearance of the first symptoms. As disease-modifying therapies for DMD become available that are ideally started early before irreversible muscle damage occurs, the importance of avoiding diagnostic delay increases. Shortening the time to a definite diagnosis in DMD allows timely genetic counseling and assessment of carrier status, initiation of multidisciplinary standard care, timely initiation of appropriate treatments, and precise genetic mutation characterization to assess suitability for access to drugs targeted at specific mutations while reducing the emotional and psychological family burden of the disease. This comprehensive literature review describes the early signs of impairment in DMD and highlights the bottlenecks related to the different diagnostic steps. In summary, the evidence suggests that the best mitigation strategy for improving the age at diagnosis is to increase awareness of the early symptoms of DMD and encourage early clinical screening with an inexpensive and sensitive serum creatine kinase test in all boys who present signs of developmental delay and specific motor test abnormality at routine pediatrician visits.